Pattern of ocular morbidity in patients attending ophthalmic OPD at tertiary care hospital, Valsad, Gujarat - Patel, Mitali G.; Mahyavanshi, Darshankumar K.; Nayak, Sunil; Patel, Aayushi; Patel, Brijal; Darji, Harsh (International Journal Of Community Medicine And Public Health, 2018)
Background: Vision is the most important special sense in human being. Normal vision is essential for normal physical, mental, psychological development and education. Causes of the preventable blindness are often the result of a combination of factors such as poverty, lack of education and inadequate health-care services. The objectives of the study were to determine the pattern of ocular morbidity in patient attending ophthalmic OPD and to find out the association of most common ocular morbidity with different variables. Methods: The cross sectional study was conducted in ophthalmic department at GMERS medical college, Valsad, Gujarat, India. It is a part of the research activity during internship period in Community Medicine department. All patients who attended ophthalmic OPD in third week of April at this hospital were enlisted in this study with their consent. The patients were seen in ophthalmic OPD by ophthalmologist, proper anterior and posterior segment evaluation was done. Data includes registration number, name, gender, education, locality, occupation, H/o systemic illness, refractive error and the diagnosis. Results: In majority of patients attending ophtahlmic OPD were with occular morbidity specifically refractory error and cataract i.e. 54% and 50% respectively. The prevalence of cataract is significantly lesser in <40 years of age, as it is an age related disease. Second most common occular morbidities observed in our study period was conjunctivitis. Cataract has correlation with age, rural locality and female preponderance. Conclusions: Majority of ocular morbidity were either preventable or treatable. Cataract (65 patients out of 130) being the commonest. If detection is early in the course, prevalence of ocular morbidity can be greatly reduced. The leading causes of ocular morbidity in our study were cataract, a conjunctivitis, and refractive error. A large number of OPD patients were constituted by follow up of cataract surgeries.